2019
DOI: 10.1080/02640414.2019.1683385
|View full text |Cite
|
Sign up to set email alerts
|

Impact of performing heavy-loaded barbell back squats to volitional failure on lower limb and lumbo-pelvis mechanics in skilled lifters

Abstract: Impact of performing heavy-loaded barbell back squats to volitional failure on lower limb and lumbo-pelvis mechanics in skilled lifters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 21 publications
4
11
0
Order By: Relevance
“…Alternatively, the mean moment increased at the hip and lumbopelvis and decreased at the knee during the flat-heel condition. This finding for the flat-heel condition aligns with what we have previously reported (2) and indicates that compensatory changes may be taking place as the knee musculature is physically stressed. Thus, the way in which the squat dynamics changed with exhaustion seems to differ based on the type of footwear.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Alternatively, the mean moment increased at the hip and lumbopelvis and decreased at the knee during the flat-heel condition. This finding for the flat-heel condition aligns with what we have previously reported (2) and indicates that compensatory changes may be taking place as the knee musculature is physically stressed. Thus, the way in which the squat dynamics changed with exhaustion seems to differ based on the type of footwear.…”
Section: Discussionsupporting
confidence: 92%
“…When squatting with a raised heel, power output decreased between T second and T final at all 3 lower-limb joints. When squatting with a flat heel, power output decreased between T second and T final at the hip and knee, which aligns with what we have previously reported for a flat-heel shoe condition (2). When the shoe conditions were compared, we found that the concentric power output at the knee was significantly less at T final during the raised-heel condition.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations